Belief in God, Confidence in the Church and Secularization in Scandinavia. (2nd June 2021) - Lemos, Carlos; Puga-Gonzalez, Ivan
We used the three latest rounds of the religion module of International Social Survey Programme to study secularization in Denmark, Norway, and Sweden, focusing on belief in God. We restricted our sample to the affiliated with the majority Protestant churches and the unaffiliated and analyzed the trends toward disaffiliation and disbelief in God. Then, we studied the association between confidence in churches, religious/secular upbringing, and demographic controls with belief in God using multinomial logistic regression models. Our treatment of belief in God as a nominal variable allowed the inclusion of both the element of doubt and different images of God in the analyses. The trends toward disbelief in God and disaffiliation suggest that secularization in Scandinavia accelerated in 2008–2018 relative to 1998–2008. In Norway, these trends were already significant in 1998–2008. Disaffiliation and disbelief in God are strongly associated, as both 'believing' and 'belonging' decayed in the three countries and seem to be strongly intertwined. We found that confidence in churches, and the frequency of attendance at church services (even if only about yearly) during the formative years are powerful predictors of belief in God. The strength of the association between confidence and attitude toward the church's power in society suggests that these two variables are fundamental to the conceptualization of belonging in the Scandinavian countries and very likely in a more general context.